Automação da ventilação em sistema compost barn: implicações no comportamento e fisiologia térmica de vacas leiteiras - Rosler, Jucemara Aparecida (2021)
Compost bedded pack barn (compost barn) system has been increasingly used for milk production in the south region of Brazil. However, acclimatizing systems are still consisted of manual activation of ventilators, which results in variations of the thermal conditions to lactating cows. Research involving automation and evaluations of thermal parameters to activate these systems are scarce. Based on the exposed, the aim of this work was to evaluate if different ventilation programs, based on temperature and air humidity, have influence on microclimate, thermal comfort and behaviour of lactating cows in compost barn system. Experiment was performed between February and March 2020, in a milk production unit located in São Jorge D’Oeste Municipality, Paraná State. In this experiment, 26 lactating cows were evaluated, submitted to four ventilation treatments, in which the system was activated automatically when temperature and air humidity thresholds were reached. Studied treatments were 25 °C/70% (temperature/air relative humidity), 25 °C/50%, 23°C/70% e 23 °C/50%. Each treatment lasted one week, and during this time data was collected about temperature, humidity, wind speed inside and outside of the compost barn, thermal comfort indexes (TemperatureHumidity Index - ITU, Black Globe TemperatureHumidity Index – ITGU, and Radiant Heat Load - CTR). The quality of bedding was evaluated with its internal and superficial temperature, and humidity. Cows were evaluated regarding their superficial body temperature, respiratory rate, and milk production. Their behaviour was evaluated by video recordings for 24 hours. As for the thermal environment, treatment 25 °C/70% resulted in lower CTR (470 W m2). Treatment 23°C/70% was efficient to reduce internal air temperature after 18 hours, but no treatment reduced the internal temperature when compared to the external temperature, and none reduced relative humidity in the warmest times. Physiological responses were observed in treatment 23 °C/70%, indicating thermal stress with average superficial body temperature above 35 °C and respiratory rate above 70 mov. min1. The lower superficial bedding temperature (22 °C) and the lower internal bedding temperature (45 °C) were registered in treatment 25 °C/70%. Behavioural responses in treatment 25 °C/70% resulted in cows ruminating while laying down longer during the night time (probability 0,8) and the afternoon time (lasting 50 minutes). Other treatments 25 °C/50% (probability 0,3), 23 °C/70% (probability 0,2) and 23 °C/50% (probability 0,3) resulted in more standing behaviour, which indicates thermal stress. We concluded that the ventilation systems interfere on the microclimate, bedding variables, thermoregulation and behaviour of cows housed in compost barn, and treatment 25 °C/70% presented the most favourable results regarding thermal comfort of dairy cows.